Analisis Faktor Manajerial Yang Berhubungan Dengan Kinerja Tenaga Kesehatan di Puskesmas - Sukarsih Sukarsih; Rizki Yeni Wulandari; Sugiyanto Sugiyanto; Wisnu Probo Wijayanto (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
Public Health Centers (Puskesmas) as primary health care facilities have a strategic role in achieving the Minimum Service Standards and national health program targets. The success of Puskesmas is strongly influenced by the performance of health workers, which is determined not only by individual competence but also by managerial factors such as leadership, work motivation, employment status, and work culture. This study aimed to analyze the relationship between these managerial factors and the performance of health workers at UPT Puskesmas Rebang Tangkas, Way Kanan Regency. This study used a quantitative approach with a cross-sectional design. The study population consisted of all health workers at UPT Puskesmas Rebang Tangkas, totaling 53 respondents, using a total sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate analyses with the Gamma correlation test at a 95% confidence level. The results showed that leadership (p = 0.043; r = 0.512), work motivation (p = 0.043; r = 0.512), and work culture (p < 0.001; r = 0.795) had significant relationships with the performance of health workers. Work culture showed the strongest relationship. Meanwhile, employment status did not show a significant relationship with health worker performance (p = 0.250). In conclusion, the performance of health workers in Puskesmas is more influenced by managerial factors, particularly leadership, work motivation, and work culture. Strengthening Puskesmas management through effective leadership, increased motivation, and the development of a positive work culture is necessary to improve the performance of health workers sustainably.